Catheter ablation of left‐sided accessory pathways in small children. Issue 5 (2nd August 2019) - Fogelman, Rami; Birk, Einat; Dagan, Tamir; Fogelman, Michal; Einbinder, Tom; Bruckheimer, Elchanan; Swissa, Moshe
Abstract: Background: Accessory pathways (APs) are a common reason for supraventricular tachycardia in small children. Trans‐septal puncture (TSP) approach is commonly used for the ablation of left‐sided APs, however it may be challenging in small children. The aim of this study was to assess the efficacy and safety of trans‐septal approach radiofrequency (RF) ablation of left‐sided APs in children weighing up to 30 kg. Methods: Of the 658 children who underwent catheter ablation of APs since 06/2002, 86 children had left‐sided AP and weighed less than 30 kg. TSP approach guided with TEE and fluoroscopy was used for left atrium access. Results: The mean age, height, and body weight were 7.6 ± 1.9 years, 122.4 ± 9.3 cm and 24.0 ± 4.2 kg, respectively. Forty‐three children (50%) were male, 46 of 86 (53%) had manifest AP, 17 of 86 (20%) weighed less than 20 kg and in 24 of 86 children (28%) a three‐dimensional system (3DS) was used to reduce fluoroscopy time. The acute success rate was 98.8% (85/86), with a recurrence rate of 2.4% (2/85) in a mean follow‐up of 66.2 ± 42.7 (9.1‐184.2) months. The mean procedure time and fluoroscopy time were significantly lower for the 3DS group compared to the standard fluoroscopy group 131 ± 41 (55‐262) and 2.4 ± 1.5 (1‐6) minutes vs 164 ± 51 (62‐249) and 27 ± 13 (8‐77) minutes, P  < 0.01 and P  < 0.0001, respectively. There were no ablation‐related complications. Conclusions: RF ablation of left‐sided APs using TSP approach in small children had an excellent efficacy and safety profile. The use of 3DS significantly reduces the procedure and fluoroscopy time.